Penerapan model pembelajaran flipped classroom terhadap hasil belajar siswa pada materi suhu dan perubahannya - Supartin Supartin; Dewi Diana Paramata; Andi Iskandar; Mohamad Jahja; Muhammad Yusuf; Dewa Gede Eka Setiawan (Universitas Hamzanwadi, 2022)
The ability of teachers to choose learning strategies is an essential and significant concern. In this case, the use of technology in learning. However, not many teachers still use the old strategy, so it is necessary to test with the application of new strategies in the learning process. The intended application of the new strategy is the application of the flipped classroom learning model. The purpose of this study was to determine the differences in student learning outcomes between classes using the flipped classroom learning model and classes using conventional learning models at SMP N 2 Bolangitang Timur. This study used an experimental method with a pretest-posttest control group design. Samples or subjects were taken using the quota sampling technique, namely class VII A and VII B. The data analysis technique consisted of a normality test, homogeneity test, t-test and n-gain test. The results showed that both data were normally distributed and had a homogeneous variance. The t-test analysis at the significant level (α = 0.05) got the results where t0 = 2.24 ta = 2.02 so that H0 was rejected and H1 was accepted. So it can be concluded that there are differences in student learning outcomes between classes that use the flipped classroom learning model and classes that use conventional learning models at SMP N 2 Bolangitang Timur.